A comparative life history study of two mirid bugs preying on Tuta absoluta and Ephestia kuehniella eggs on tomato crops: Implications for biological control - Mollá-Hernández, Óscar; Biondi, Antonio; Alonso-Valiente, Miquel; Urbaneja, Alberto (2017)
The omnivorous predators Nesidiocoris tenuis (Reuter) and Macrolophus pygmaeus Rambur (Hemiptera: Miridae) are indigenous natural enemies that commonly inhabit tomato crops in the Mediterranean basin. Both predators are mass-reared and primarily released to control whiteflies, although recently they have also contributed to the control of the invasive tomato pest Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae). The life history traits of these two predators have been studied in the laboratory under the conditions of being fed exclusively the eggs of T. absoluta or the eggs of the factitious prey Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae). Immature stages of both predator species successfully developed while preying on eggs of T. absoluta. However, the mature M. pygmaeus females produced significantly lower numbers of offspring in comparison to the offspring produced when preying on E. kuehniella eggs. This resulted in higher than expected demographic indexes for N. tenuis when compared to M. pygmaeus (e.g., the intrinsic rates of increase were 0.127 and 0.005, respectively). Our results support previous studies on the potential of N. tenuis has as biological control agent of T. absoluta, and indicate that the role of M. pygmaeus in controlling T. absoluta in the absence of other food sources is possibly limited. © 2013 International Organization for Biological Control (IOBC).